2018
DOI: 10.22270/jddt.v8i5.1879
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Double-Blind Placebo-Controlled Study of Folic Acid Adjunct for 8 Weeks in Hyperhomocysteinaemic Hypertensive Patients in Zaria, Nigeria

Abstract: Objectives: This study was aimed at determining the effect of folic acid adjunct therapy on homocysteine (HCY) and blood pressure (BP) levels in hypertensive subjects. Method: The study was a double blind placebo-controlled trial on 100 hypertensive patients randomised into 50 folate and 50 placebo groups, where the folate group had 5 mg folic acid daily for 8 weeks. Fasting plasma homocysteine, folate and blood pressure levels were determined at baseline, at 4 and at 8 weeks. The Mixed Model Repeated Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 26 publications
(47 reference statements)
1
14
1
Order By: Relevance
“…These they also add to their staple diet as these are readily available and cheaper 43,44 . Additionally, deficiencies in other B vitamins like B 12 and B 6 which can result in hyperhomocysteinemia will require further investigation in subsequent studies as they were not assayed in the present study; however some study done in Nigeria had shown that B 12 deficiency was rare in Nigerians 30,45,46 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These they also add to their staple diet as these are readily available and cheaper 43,44 . Additionally, deficiencies in other B vitamins like B 12 and B 6 which can result in hyperhomocysteinemia will require further investigation in subsequent studies as they were not assayed in the present study; however some study done in Nigeria had shown that B 12 deficiency was rare in Nigerians 30,45,46 .…”
Section: Discussionmentioning
confidence: 93%
“…It becomes imperative that other non-traditional vascular risk factors should be looked out for. Also, lifestyle modification inclusive of increased consumption of high fibre, fruits & vegetables, exercise and avoidance of smoking /alcohol should be emphasized, as part of the cardiovascular disease preventive strategy 30,50 . Traditional vascular risk factors associated with hyper-tension like hyperlipidaemia were not determined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, a study by Vander Jagt on adolescent girls in Northern-Nigeria showed that folate levels were within satisfactory limits despite high mean homocysteine levels and this was attributed to their marginal vitamin B12 status. 33 This may not extrapolate for an adult population as adolescent girls were studied 20 but previous study by Flemming et al 20,40,50 showed that vitamin B12 deficiency was rare in Northern-Nigerians. 20,40 This was confirmed by a recent study done in Zaria comparing stroke patients with normal healthy subjects which showed that vitamin B12 deficiency is not the problem of healthy Nigerians as the levels were well within normal reference range.…”
Section: Discussionmentioning
confidence: 99%
“…33 This may not extrapolate for an adult population as adolescent girls were studied 20 but previous study by Flemming et al 20,40,50 showed that vitamin B12 deficiency was rare in Northern-Nigerians. 20,40 This was confirmed by a recent study done in Zaria comparing stroke patients with normal healthy subjects which showed that vitamin B12 deficiency is not the problem of healthy Nigerians as the levels were well within normal reference range. 43 Further studies on hypertensive subjects should be done to determine if there are any such deficiencies in them which is currently on-going.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation